Gender Differences in Cardiogenic Shock Patients: Clinical Features, Risk Prediction, and Outcomes in a Hub Center - Lozano-Jiménez, Sara; Iranzo-Valero, Reyes; Segovia-Cubero, Javier; Gómez-Bueno, Manuel; Rivas-Lasarte, Mercedes; Mitroi, Cristina; Escudier-Villa, Juan Manuel; Oteo-Dominguez, Juan Francisco; Vieitez-Florez, Jose María; Villar-García, Susana; Hernández-Pérez, Francisco José (Frontiers in Cardiovascular Medicine, 2022)
There is scarce knowledge about gender differences in clinical presentation, management, use of risk stratification tools and prognosis in cardiogenic shock (CS) patients. The primary endpoint was to investigate the differences in characteristics, management, and in-hospital mortality according to gender in a cohort of CS patients admitted to a tertiary hub centre. The secondary endpoint was to evaluate the prognostic performance of the Society of Cardiovascular Angiography and Interventions (SCAI) classification in predicting in-hospital mortality according to sex. This is a retrospective single-centre cohort study of CS patients treated by a multidisciplinary shock team between September 2014 and December 2020. Baseline characteristics and clinical outcomes according to gender were registered. Discrimination of SCAI classification was assessed using the area under the receiver operating characteristic curve (AUC). Overall, 163 patients were included, 39 of them female (24%). Mean age of the overall cohort was 55 years (44-62), similar between groups. Compared with men, women were less likely to be smokers and the prevalence of COPD and diabetes mellitus was significantly lower in this group (p<0.05). Postcardiotomy (44% vs 31%) and fulminant myocarditis (13% vs 2%) were more frequent aetiologies in females than in males (p=0.01), whereas AMI was less common among females (13% vs 33%). Regarding management, the use of temporary mechanical circulatory support, mechanical ventilation or renal replacement therapy was frequent and no different between the groups (p>0.05). In-hospital survival in the overall cohort was 53%, without differences between groups (52% in females vs 55% in males, p=0.76). Most of the patients (60,7%) were in SCAI E at presentation without differences between sexes. The SCAI classification showed a moderate ability for predicting in-hospital mortality (AUC: 0.653, 95% CI 0.582- 0.725). The AUC was 0.636 for women (95% CI 0.491- 0.780) and 0.658 for men (95% CI 0.575- 0.740). Only one in four of patients treated at a dedicated CS team were female. In this very high-risk CS population of multiple aetiologies, overall in-hospital survival was slightly above 50% and showed no differences between sexes. Treatment approaches, procedures and SCAI risk stratification performance did not show gender disparities among treated patients.